Amrubicin is effective against small cell carcinoma of the prostate as a second‐line chemotherapeutic agent: A case report. Issue 3 (7th March 2019) - Maesaka, Fumisato; Nakai, Yasushi; Tomizawa, Mitsuru; Owari, Takuya; Miyake, Makito; Inoue, Takeshi; Anai, Satoshi; Tanaka, Nobumichi; Fujimoto, Kiyohide
Abstract : Introduction: Small cell carcinoma of the prostate has a poor prognosis. Furthermore, treatments for small cell carcinoma of the prostate have not been established. We report a case where amrubicin was effective for second‐line chemotherapy. Case presentation: A 50‐year‐old man complaining of painful micturition was referred to our hospital. Due to high prostate‐specific antigen level (16.57 ng/mL) and abnormal magnetic resonance imaging findings (cT2c), prostate biopsy was performed; mixed adenocarcinoma and small cell carcinoma of the prostate were observed. Radical prostatectomy was performed following a cT2cN0M0 diagnosis. One month after prostatectomy, fluorodeoxyglucose positron emission tomography/computed tomography showed metastatic lesions in the bone; the patient received androgen deprivation therapy and two cycles of cisplatin plus irinotecan. Due to new metastatic lesions and sustained abnormal pro‐gastrin‐releasing peptide levels, amrubicin was administered for second‐line chemotherapy. Pro‐gastrin‐releasing peptide was normalized and positron emission tomography/computed tomography showed a complete metabolic response after 15 cycles of amrubicin. Conclusion: Amrubicin could serve as a second‐line chemotherapeutic agent against small cell carcinoma of the prostate.